2011
DOI: 10.1210/en.2010-0768
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inactivation of the Androgen Receptor Gene in Murine Proximal Epididymis Causes Epithelial Hypotrophy and Obstructive Azoospermia

Abstract: Androgen receptor function is required for normal differentiation and maintenance of the proximal epididymis, and its ablation results in obstructive azoospermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 31 publications
5
41
0
Order By: Relevance
“…Our previous study and unpublished data have shown that Ar expression is also reduced in Lgr4 mutant epididymal epithelium (Li et al, 2010). Epididymal-specific deletion of Ar resulted in epithelial hypoplasia and hypotrophy and led to male infertility, similar to the phenotype observed in adult Lgr4 mutant mice (Krutskikh et al, 2011;Mendive et al, 2006).…”
Section: Discussionsupporting
confidence: 51%
“…Our previous study and unpublished data have shown that Ar expression is also reduced in Lgr4 mutant epididymal epithelium (Li et al, 2010). Epididymal-specific deletion of Ar resulted in epithelial hypoplasia and hypotrophy and led to male infertility, similar to the phenotype observed in adult Lgr4 mutant mice (Krutskikh et al, 2011;Mendive et al, 2006).…”
Section: Discussionsupporting
confidence: 51%
“…In the second model, RNase10-Cre was used to conditionally knock out Frs2. RNase10 was identified as the gene expressed particularly in the proximal epididymis [15]; a recent knock out study indicated it is involved in sperm maturation [16]. Expression of RNase10-Cre begins on approximately P17 with strong expression in the IS and proximal caput but wanes gradually distally without a distinct border [15].…”
Section: Introductionmentioning
confidence: 99%
“…While several transcription factors have been shown to be expressed in the developing epididymis [8,9], it remains unclear which, if any of these, establish the segment-specific gene expression patterns in the epididymis. One appealing candidate is the transcription factor, androgen receptor (AR), which clearly has a role in the development of the epididymis [6,10], but it remains to be determined whether it controls any segment-specific developmental events. Other promising candidates to have a role in this are the homeobox transcription factors HOXA10 and HOXA11 since their loss in mice causes region-specific epididymal defects, including ''homeotic transformation events,'' in which one segment acquires the appearance of another segment or organ [11].…”
Section: Introductionmentioning
confidence: 99%